P130 Treatment of SLE with the immunoproteasome inhibitor KZR-616: results from the first 4 cohorts of the MISSION study, an open-label phase 1b dose escalation trial. (23rd March 2020) - Furie, Richard; Parikh, Samir V; Maiquez, Adonis; Khan, Amber; Moreno, Orlando; Soneira, Miguel; Kirk, Christopher; Bomba, Darrin; Harvey, Kenneth; Farmer, Mary Katherine
Abstract : Background: Subcutaneous (SC) administration of KZR-616 (30 and 45 mg weekly [QW]) was demonstrated as safe and well-tolerated, and successfully achieved target levels of immunoproteasome inhibition in healthy volunteers. 1, 2 Methods: SLE patients in this open-label multicenter dose escalation trial received KZR-616 at doses of 45 mg (Cohort 1), 60 mg (Cohort 2), or 30 mg with escalation to 60 mg (Cohorts 2a and 2b) subcutaneously weekly through Week 13 (W13) with 12 weeks of follow-up. Results: As of 16 January 2020, 33 patients had enrolled and received at least 1 dose of KZR-616. The majority of TEAEs have been mild or moderate with no reported peripheral neuropathy, prolonged GI-related AEs, and no clinically significant laboratory AEs. When compared to baseline, improvement in measures of disease activity were seen at W13 and beyond. A single patient with active class IV/V nephritis who failed prior treatment with tacrolimus was enrolled on prednisone 10 mg, leflunomide 10 mg, and hydroxychloroquine 200 mg/day; nephrotic-range proteinuria at baseline (3.85 g/day) decreased to 0.6 g/day 4 weeks after the last dose of KZR-616. Conclusions: Weekly SC administration of KZR-616 at 45 and 60 mg was safe and well-tolerated. Evidence of disease suppression at W13 was observed, and 94% of evaluable patients had improvements on at least 2 measures/assessments of disease activity. In addition, one study participant with active proliferative nephritis (LN) was enrolled with significant reduction in proteinuria. The Phase 2 portion of this study in active proliferative LN is open for enrollment. References: Lickliter J. et al. Ann Rheum Dis 2018;77: A1413 Furie R, et al. Ann Rheum Dis 2019;78: A776